2006
DOI: 10.1111/j.1467-3010.2006.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and type 2 diabetes

Abstract: The rise in obesity -and specifically abdominal obesity -is driving the global increase in type 2 diabetes. Excess visceral fat, the causative factor behind abdominal obesity, is closely linked with β -cell dysfunction and insulin resistance, two of the key components of type 2 diabetes pathogenesis. Attempts to curb the current abdominal obesity and type 2 diabetes epidemics will require a government-led public health approach, in tandem with a personal approach aimed at helping abdominally obese individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…9,10,14,26 Many studies have documented that VF is associated with increased incidence of metabolic syndrome and has significantly stronger relation with insulin resistance and diabetes. [7][8][9][10]14,19 Findings in this study corroborates with previous studies as this study (table 2) shows that visceral fat has a stronger association with development of diabetes compared to subcutaneous fat independent of measurement site.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…9,10,14,26 Many studies have documented that VF is associated with increased incidence of metabolic syndrome and has significantly stronger relation with insulin resistance and diabetes. [7][8][9][10]14,19 Findings in this study corroborates with previous studies as this study (table 2) shows that visceral fat has a stronger association with development of diabetes compared to subcutaneous fat independent of measurement site.…”
Section: Discussionsupporting
confidence: 91%
“…[15][16][17][18] Others have documented that VF is associated with an increased incidence of metabolic syndrome and has significantly stronger relation with insulin resistance and diabetes. [7][8][9][10]14,19 SCF is not consistently reported to be a significant correlate of metabolic syndrome or its individual component. However, some [20][21][22][23][24] studies have shown associations between SCF, insulin resistance and diabetes.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Overweight individuals with a family history of type‐2 diabetes and those with excessive abdominal girth are at increased risk for developing diabetes (Appel, Jones, & Kennedy‐Malone, ; Frayn, ; Liu et al, ; Waine, ). Weight loss is purported to reduce the risk of progression to diabetes in this population; however, most studies have not clearly shown that weight‐loss, itself, is beneficial to health or that it can be maintained in obese individuals over time.…”
Section: Introductionmentioning
confidence: 99%